2021
DOI: 10.1021/jacs.0c10000
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Carrier Transport Properties Across Horizontally vs Vertically Oriented Heterostructures of 2D/3D Perovskites

Abstract: Two-dimensional-on-three-dimensional (2D/3D) halide perovskite heterostructures have been extensively utilized in optoelectronic devices. However, the labile nature of halide perovskites makes it difficult to form such heterostructures with well-defined compositions, orientations, and interfaces, which inhibits understanding of the carrier transfer properties across these heterostructures. Here, we report solution growth of both horizontally and vertically aligned 2D perovskite (PEA)2PbBr4 (PEA = phenylethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 63 publications
(109 reference statements)
0
63
0
Order By: Relevance
“…Zhao et al 38 fabricated a 2D/3D perovskite composite by adding Cs + to 2D (PEA) 2 PbBr 4 nanoplate, which combined the excellent stability of 2D perovskites and low exciton binding energy of 3D perovskites and was promising for practical LEDs. Wright et al 39 reported the heterostructure of both horizontally and vertically aligned perovskite (PEA) 2 PbBr 4 grown on 3D CsPbBr 3 in solution, which provided an ideal platform to study the physical properties and cross-heterojunction charge transfer process in a more explicit 37 ; (e). Morphology of perovskite thin films (The scale bar is 10 μm.).…”
Section: Fabrication Of 2d Perovskite Composites 21 General Fabrication Methodsmentioning
confidence: 99%
“…Zhao et al 38 fabricated a 2D/3D perovskite composite by adding Cs + to 2D (PEA) 2 PbBr 4 nanoplate, which combined the excellent stability of 2D perovskites and low exciton binding energy of 3D perovskites and was promising for practical LEDs. Wright et al 39 reported the heterostructure of both horizontally and vertically aligned perovskite (PEA) 2 PbBr 4 grown on 3D CsPbBr 3 in solution, which provided an ideal platform to study the physical properties and cross-heterojunction charge transfer process in a more explicit 37 ; (e). Morphology of perovskite thin films (The scale bar is 10 μm.).…”
Section: Fabrication Of 2d Perovskite Composites 21 General Fabrication Methodsmentioning
confidence: 99%
“…Previous studies have shown that the n = 1 phase tends to be aligned parallel to the substrate and is unfavorable for carrier transport in the device. 48 This peculiarity may indicate efficient charge transport in these three films. A key merit of the PMAI : FAI ratio in precursors is that a higher FAI ratio leads to the transformation of dominant layered perovskites from PMA 2 FA nÀ1 Pb n I 3n+1 to FA 2 FA nÀ1 Pb n I 3n+1 .…”
Section: Energy and Environmental Science Papermentioning
confidence: 94%
“…[21] Besides, Wright et al fabricated a horizontally versus vertically oriented heterostructures of 2D/3D perovskites and carrier transport properties were studied in detail. [22] Xu et al developed a highly controllable homoepitaxial growth method of hybrid perovskites for LED arrays. [23] The dry and wet etching and vapor deposition process could result in accurately controlled and highly ordered patterned structures, but these arrays growth always required complex fabrication process and equipment when scale up fabrication.…”
Section: Doi: 101002/smll202107915mentioning
confidence: 99%
“…fabricated a horizontally versus vertically oriented heterostructures of 2D/3D perovskites and carrier transport properties were studied in detail. [ 22 ] Xu et al. developed a highly controllable homoepitaxial growth method of hybrid perovskites for LED arrays.…”
Section: Introductionmentioning
confidence: 99%